A supply chain coordination mechanism for common items subject to failure in the electronics, defense, and medical industries - Sher, Mikhail M.; Kim, Seung-Lae; Banerjee, Avijit; Paz, Michael T. (International journal of production economics, 2018)
Prior research on inventory management for imperfect items assumes that such items can be dealt with through salvage or rework. Increased repair costs and decreased production costs arising from modern production processes (e.g. miniaturization, 3D printing), however, have led suppliers to increasingly eschew such solutions in favor of items and components which are discarded upon failure rather than being reworked or scrapped. In this paper, we first determine optimal supplier and buyer inventory policies for items which fail and which cannot be reworked. We then develop a supply chain coordination mechanism which uses a common replenishment time to coordinate a supply chain consisting of a single supplier and n buyers. Our coordination mechanism yields a global minimum for system-wide costs. Numerical examples are provided to illustrate important conditions under which our model is particularly effective at reducing system-wide costs. •We coordinate a supply chain for items common to defense, electronics and medical industries.•These items fail with a known probability and are not subject to rework.•Supply chain coordination is achieved via common replenishment time.•Bisection algorithm is utilized to coordinate the supply chain.•We minimize system-wide costs for a supply chain with one supplier and n buyers.